Participatory Approaches for the Transition from Automation to Artificial Intelligence (AI): A Case Study - Calicchia, Sara; Colagiacomo, Chiara; Bagnato, Angela; Pistagni, Roberta; Papaleo, Bruno; Grosso, Francesca (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
To balance technological progress with worker well-being, it is essential to maintain human-centered spaces for participation and integrate traditional safety programs with health promotion initiatives that empower workers. This study presents a participatory workshop conducted in an Italian automotive company, where workers, managers, and experts collaborated to improve working conditions, taking into consideration AI-based solutions as well. Through experience mapping and structured dialogue, concrete solutions emerged to optimize processes and enhance well-being. The results indicate improvements in work organization and interpersonal relationships, fostering greater trust in technological change. A participatory approach is a key strategy for integrating AI technologies fairly and inclusively, enhancing decision- making and worker engagement.